2022
DOI: 10.1039/d1cp05829k
|View full text |Cite
|
Sign up to set email alerts
|

Structural adaptations in the bovine serum albumin protein in archetypal deep eutectic solvent reline and its aqueous mixtures

Abstract: The global concern over the environmental impact and challenges associated with the use of conventional solvents in bio-transformation processes have pushed the search for alternative solvents. Recently, deep eutectic solvents...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…75 Here, it is observed that the change in the emission of the Trp residues of BSA in 1:2 ChCl:Glyc is opposite to that of the isolated amino acid. As most of these residues are buried in the hydrophobic core of the protein in the native state, 51,55,74 these changes cannot be solely attributed to solvent exposure and must relate to conformational transitions occurring in the protein, where the Trp side chains are relocated inside the protein envelope. In contrast, the bathochromic shifts observed at low hydration potentially relate to an increase in the solvent exposure of Trp and a more pronounced unfolding.…”
Section: ■ Resultsmentioning
confidence: 99%
“…75 Here, it is observed that the change in the emission of the Trp residues of BSA in 1:2 ChCl:Glyc is opposite to that of the isolated amino acid. As most of these residues are buried in the hydrophobic core of the protein in the native state, 51,55,74 these changes cannot be solely attributed to solvent exposure and must relate to conformational transitions occurring in the protein, where the Trp side chains are relocated inside the protein envelope. In contrast, the bathochromic shifts observed at low hydration potentially relate to an increase in the solvent exposure of Trp and a more pronounced unfolding.…”
Section: ■ Resultsmentioning
confidence: 99%
“…This result is similar to the findings by Kumari et al , who observed that choline chloride–urea could form H bonds with BSA and affect its secondary structure; however, the protein backbone was preserved. 71…”
Section: Resultsmentioning
confidence: 99%
“…Rigidity in the protein structure is also noted in the presence of pure reline. The authors concluded that, despite the expansion, the tertiary structure of BSA in pure reline was similar to the native protein structure [59].…”
Section: Stability Of Proteins In Deep Eutectic Solventsmentioning
confidence: 99%
“…More recently, the effect of pure and hydrated reline choline chloride/urea DES in the structural stability of BSA using all-atom molecular dynamics simulations was investigated by Kumari et al [59]. A considerable change in the BSA structure and an increment in the accessible surface area of the solvent were found.…”
Section: Stability Of Proteins In Deep Eutectic Solventsmentioning
confidence: 99%